Reliability of Schirmer and Phenol Red Thread test value on dry eye patients - Urvashni Nirghin; Tharuna Govender; Yeshalya Hirachund; Rorisang Mosololi; Hlengiwe Nxumalo; Sumaya Patel; Philani Zwane; Khathutshelo P. Mashige (African Vision and Eye Health)
Background: The repeatability of the Schirmer test (ST) and Phenol Red Thread test (PRT) has been investigated thoroughly on patients with normal tear function; however, it is limited to dry eye patients.